Asymmetrical Recovery in Cities After Disaster. The Lower Ninth Ward in New Orleans After Hurricane Katrina - Kammerbauer, Mark (Raumforschung und Raumordnung | Spatial Research and Planning, 2014)
When flood events trigger disaster in cities, the recovery process constitutes a complex field of activity covering urban space, state institutions, and impacted citizens. Recovery may not occur evenly, but instead, asymmetrically. In the case of the city of New Orleans in the USA, heavily hit by Hurricane Katrina in 2005, this can be observed particularly in the city’s Lower Ninth Ward. Here, a rebuilding program oriented towards homeowners was supposed to enable citizens to return. Why couldn’t the plans and programs for recovery prevent the emergence of asymmetric recovery in the Lower Ninth Ward? This paper shows that these plans and programs didn’t adequately respond to urban spatial and social conditions and weren’t oriented towards the vulnerability of impacted citizens. For this purpose, empirical data collected via quantitative and qualitative methods in 2007 and 2009 are featured here. The aim is to support knowledge-based planning recommendations that address the vulnerability of impacted citizens and to contribute to a discussion on just and sustainable recovery in and of cities after disaster.